Entry and Competition in the Market for Short-Cycle Programs - Carranza, Juan Esteban (World Bank, Washington, DC, 2021)
Short-cycle higher education programs form skilled human capital in two or three years and are eminently oriented to the labor market. While they could play a key role in the upskilling and reskilling of the workforce required for employment recovery after the COVID-19 pandemic, they will only do so if their supply responds fast and nimbly to the skill needs to local labor markets. This paper studies the entry, competition, and turnover of short-cycle higher education programs (SCPs) in Colombia. It documents a large expansion in the number of programs over the past fifteen years and studies the frequency of program entry and exit. It finds that the market for SCPs is more dynamic than the market for bachelor's programs, as it exhibits greater turnover or “churn" of programs, with a significantly higher rate of program entry and exit in a given year. Exploiting data on local productivity and employment by field of study, the paper finds that SCPs are more responsive than bachelor's programs to changes in local labor demand. Among SCP providers, private and non-university institutions respond the most to the local economy. SCP entry is deterred by the presence of competitors and responds to cost considerations, particularly among private institutions. For a given institution, exit and entry decisions are highly correlated within a field of study. While enrollment is sensitive to the number of competitors, institutions differentiate their product by tuition, field, and geographic coverage. Overall, the evidence suggests that SCPs might indeed respond fast and nimbly to the local labor market needs created by the pandemic.